Potential, Challenges, and Opportunities of a Philippine State University as a Farm Tourism Destination - Canson, Maria Cristina I.; Caelian, Merlita V. (Philippine Social Science Journal, 2025)
Employing an explanatory sequential mixed methods design, this study assessed the potential of a Philippine State University as a farm tourism destination using the "Six As" framework (attractions, accessibility, amenities, activities, accommodation, and accountability). Data obtained from 331 survey respondents and 8 interviewees revealed that while the university holds high potential for Department of Tourism (DOT) accreditation due to its robust agricultural program and existing attractions, it faces challenges regarding infrastructure deficiencies and inadequate amenities. The findings indicate that although significant opportunities exist for both the academe and the community, successful implementation requires deliberate tourism planning and rigorous adherence to accreditation standards. Ultimately, this research serves as a validation for agricultural universities as viable tourism sites and provides a basis for a strategic Farm Tourism Development Plan to address current limitations.